Development of an Endoscopic Ultrasound Device for Delivering Microbubble-Mediated Cavitation in the Pancreas Characterization and Preclinical In-Vivo Results - Rohfritsch, Adrien (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2025)
Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis and limited treatment options. Focused ultrasound (FUS) has shown potential for improving PDAC treatment outcomes by enhancing drug delivery through acoustic cavitation. In this article, we present the development of a prototype endoscopic ultrasound (EUS) device capable of producing microbubble-mediated cavitation with ultrasound imaging for treatment guidance. The performance of the therapy array, composed of 64 piezoelectric elements, was characterized up to voltages of 60 V peak, achieving negative pressures of 6.55 MPa in water for a focal distance of 20 mm. High image quality as well as the feasibility of generating cavitation activity in the pancreatic parenchyma were demonstrated in vivo in a porcine model. Future work will focus on demonstrating its potential as a potentiator of chemotherapeutic treatment for PDAC, paving the way for a new minimally invasive approach to PDAC treatment